PERAN MEDIA KARTU KATA BERGERAK (FLASH CARD) DALAM MENGEMBANGKAN KOSAKATA BAGI ANAK DISLEKSIA MELALUI SIMULASI ROLE PLAYING “PASAR”: STUDI KASUS DI KELAS INKLUSI SDN PRAMBON KABUPATEN MADIUN - Resti Wulandari; Jeffry Handhika; Dwi Rosita Sari (An Nafi': Multidisciplinary Science, 2026)
Students with dyslexia in inclusive classes often face specific challenges in developing vocabulary, which is the foundation for reading and writing skills. This study aims to analyze the role of moving word cards (flash cards) in developing vocabulary for dyslexic students through a "Market" role-playing simulation. This research uses a qualitative approach with a case study design, conducted in an inclusive class at SDN Prambon, Madiun Regency. Data were collected through participatory observation, in-depth interviews with classroom teachers and special accompanying teachers (GPK), and analysis of student work documents. Thematic data analysis shows that the use of flash cards in role-playing simulations provides a multi-sensory and contextual learning experience. This media helps dyslexic students in recognizing, understanding, and using new vocabulary related to market themes in a more meaningful way. The role-playing simulation creates a low-anxiety environment that encourages active verbal communication. The integration of visual, kinesthetic, and auditory elements through this media significantly supports the strengthening of lexical representations in the memory of dyslexic students. These findings offer practical implications for the use of game-based media in language learning for students with specific learning difficulties in inclusive settings.